2021
DOI: 10.1093/jpe/rtab086
|View full text |Cite
|
Sign up to set email alerts
|

Realized niche shift associated withGalinsoga quadriradiata(Asteraceae) invasion in China

Abstract: Aims Shifts in the realized niches of exotic species may play an important role in their invasion. Galinsoga quadriradiata has invaded China widely and occupied many climate zones that are different from its native range. We addressed the climatic niche shift of G. quadriradiata, and evaluated how this could contribute to its invasion in China. Methods We used the Maxent model to predict the potential distribution of G. quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Introduced species are often exposed to novel climatic conditions in their new ranges or released from competitive biotic constraints encountered in their native ranges. Rapid evolutionary change in response to these new local conditions may facilitate expansion of introduced species beyond conditions characteristic of their native range, particularly when population differentiation follows climatic gradients in the introduced range (Blossey et al 2017; Quiroga et al 2018; Zhang et al 2022). Indeed, recent studies have found evidence of population differentiation in seed germination requirements of invasive Johnsongrass [ Sorghum halepense (L.) Pers.]…”
Section: Resultsmentioning
confidence: 99%
“…Introduced species are often exposed to novel climatic conditions in their new ranges or released from competitive biotic constraints encountered in their native ranges. Rapid evolutionary change in response to these new local conditions may facilitate expansion of introduced species beyond conditions characteristic of their native range, particularly when population differentiation follows climatic gradients in the introduced range (Blossey et al 2017; Quiroga et al 2018; Zhang et al 2022). Indeed, recent studies have found evidence of population differentiation in seed germination requirements of invasive Johnsongrass [ Sorghum halepense (L.) Pers.]…”
Section: Resultsmentioning
confidence: 99%
“…Species distribution models are frequently employed to assess the potential impact of non-native species in new habitats, assuming that the climatic niche remains constant (Gallagher et al 2010). A valuable approach to elucidating the complexity of plant invasion is to contrast global and regional niches (Taucare-Ríos et al 2016; Zhang et al 2021). Reciprocal modeling from the invaded range to the native range can assist in identifying the potential origin of the biotypes that invaded a country (Suárez-Mota et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ordination techniques such as principal component analysis are adequate for the quanti cation of niche dynamics (Guisan et al 2014). These analyses, in conjunction with metrics that estimate niche emptiness, stability, and expansion, plus equivalence and similarity tests, provide an effective tool for predicting the invasive potential of alien species, their capacity to thrive and expand in novel habitats and, consequently, to identify environments or geographic areas most at risk for future invasions (Gallagher et al 2010;Dinis et al 2020;Zhang et al 2021;Aravind et al 2022). The results of the comparisons of environmental variables and the environmental PCA indicate that the native and invaded ranges of C. macrocephalum evidence similar ecological tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…It provides one of the essential foundations for invasion ecology, possibly because it unfolds the links between distributions of alien invasive species (AIS), environmental variables, and the potential range shifts of AIS under the background of global climate change (Davies et al, 2019; MacDougall et al, 2009). Ecological niche models (ENMs) are widely used to predict the potential distributions of AIS and their shifts under global change scenarios (e.g., Bellard et al, 2013; Fang et al, 2021; Luizza et al, 2016; Zhang et al, 2022), which could help us develop management strategies against the invasions of AIS. However, one of the key underlying assumptions of ENMs is the ecological niche conservatism hypothesis (Pearman et al, 2008; Petitpierre et al, 2012).…”
Section: Introductionmentioning
confidence: 99%